2014
DOI: 10.3892/ijmm.2014.1796
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grape seed proanthocyanidin extract on pentylenetetrazole-induced kindling and associated cognitive impairment in rats

Abstract: Numerous studies have demonstrated the antioxidant effects of grape seed proanthocyanidin extract (GSPE). The generation of free radicals and the ensuing apoptosis may contribute to the pathogenesis of epilepsy; therefore, in the present study, we examined the effects of GSPE on cognitive impairment and neuronal damage induced by chronic seizures in rats. Seizures were induced by a daily intraperitoneal (i.p.) injection of pentylenetetrazole (PTZ; 35 mg/kg/day, 36 days). Two other groups were treated with GSPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 45 publications
4
34
0
2
Order By: Relevance
“…Grape seed proanthocyanidin extract (GSE) is extracted from grape seeds which contained favorable amounts of polymerized oligomers, polyphenolic flavonoids and oligomeric proanthocyanidins. Chinese used traditional medicines and GSE for the betterment of their fitness and animal health (Zhen et al, 2014). GSE played an important role in promoting anti-mutagenic (Sharma and Katiyar 2010), myocardial protecting (Demirkaya et al, 2009) and neurons protecting (Ahn et al, 2011) ability in various experimental trials.…”
Section: Introductionmentioning
confidence: 99%
“…Grape seed proanthocyanidin extract (GSE) is extracted from grape seeds which contained favorable amounts of polymerized oligomers, polyphenolic flavonoids and oligomeric proanthocyanidins. Chinese used traditional medicines and GSE for the betterment of their fitness and animal health (Zhen et al, 2014). GSE played an important role in promoting anti-mutagenic (Sharma and Katiyar 2010), myocardial protecting (Demirkaya et al, 2009) and neurons protecting (Ahn et al, 2011) ability in various experimental trials.…”
Section: Introductionmentioning
confidence: 99%
“…Proanthocyanidin, a class of polyphenols with strong antioxidant properties commonly found in a variety of plants, have been reported to exert cell protective effects by reducing mitochondria damage and inhibiting cell apoptosis (Gao et al, 2014; Lu et al, 2015; Zhen et al, 2014). Grape seed proanthocyanidin extract (GSPE), an extract from grape seed, contains phenolic hydroxyl groups, which are well-known antioxidants (Ding et al, 2013; Mansouri et al, 2011), safe and well tolerated in humans (Sano, in press).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that GSPE exerts anti-inflammatory (Park et al, 2012; Zhou et al, 2011), anti-carcinogenic (Uchino et al, 2010), anti-mutagenic (Sharma & Katiyar, 2010), and anti-ischemia/reperfusion injury (Song et al, 2012; Wei et al, 2012) effects, as well as cardioprotective (Bagchi et al, 2003; Demirkaya et al, 2009) and neuroprotective (Ahn et al, 2011) benefits. Proanthocyanidin also contains catechin, a flavanol capable of crossing the blood–brain barrier more easily than other natural antioxidants (Zhen et al, 2014), such as quercetin (Shen et al, 2013) and curcumin (Ahmad, 2013). However, the role of GSPE on lymphocyte apoptosis via its anti-oxidative property is poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the contribution of GSE to the TAOC at low and medium levels (1 and 10 μg/mL, respectively) was moderate in unstressed or stressed IPEC1, but GSH was increased at 10 μg GSE/mL in unstressed cells, as well as at 1 and 10 μg/mL in the stressed cells. These results may represent the first direct evidence that a certain level of GSE can elevate the GSH contents in intestinal epithelial cells, although a few related studies have reported that dietary supplementation with GSE promotes an increase in GSH in the rat liver, the hippocampus and human serum [12,13] . Evidence indicates that some compositions of GSE (such as Quercetin, Epicatechin and Epicatechingallate) have the ability to stimulate GRed and γ-GCS activity, which act as the rate-limiting and key enzymes, respectively, in two major processes of GSH synthesis [14] , suggesting that GSE accelerated the synthesis of GSH.…”
Section: Discussionmentioning
confidence: 71%